Human capital and stakeholder engagement intervention: a women empowerment pathway to achieve sustainable community development in water, sanitation, and hygiene at Vaijapur Village of Karnataka, India - Pawar, Shivanand; Chougule, Mahesh; Channaveer, R. M. (Frontiers in Sustainability, 2025)
IntroductionEnhancing human capital through Social Behavior Change Communication (SBCC) strategy, and social entrepreneurship approach, strategically intends to improve knowledge, skills, and practice at the individual and community level. Grounded in human capital theory, the intervention aimed on building the capabilities of women participants to influence Water, Sanitation, and Hygiene (WASH) outcomes. Community education and stakeholder engagement played a crucial role in strengthening local capabilities and fostering sustainable WASH behaviors. Furthermore, the WASH-based program and stakeholder engagement process have the potential to reduce the risk of infection from waterborne diseases and enhance prevention and control measures within the village community.MethodologyThe study intends to measure the influence of human capital and stakeholder engagement interventions on elevating WASH knowledge, attitude, and practice among women participants. The sample size consists of women participants (N = 110) in the 20–50-year-old age group (Mean = 42.78, SD = 13.98). All the head women participants of the 110 households selected for the study kept village development as a prime focus.ResultsSignificant improvement was observed in the outcome status of the knowledge level of women in water, sanitation, and hygiene compared to their baseline status (M = 2.36, SD = 0.631, df = 109, t = 43.792, p < 0.01). A significant increase was observed in the outcome status of the attitude of women toward water, sanitation, and hygiene (M = 16.55, SD = 1.640, df = 109, t =19.755, p < 0.01). In the practice domain of WASH, the women participants showed a significant increase in the outcome status compared to their baseline status (M = 1.29, SD = 0.580, df = 109, t = 17.881, p < 0.01).ConclusionHuman capital building, social behavior change and communication strategy, stakeholder engagement and social entrepreneurship approach create a conducive environment for sustainable community development.